Why I Stopped Watching Porn. Issue 1 (June 2017) - Gavrieli, Ran
This text* is not a theoretical one; it is a result of four and a half years of serving aid to women, girls and boys in prostitution on the streets of Tel Aviv. The effort here is to connect the dots between human trafficking, prostitution and porno-graphy, and see how they are steeped in gender inequality and common tolerant notions that need deconstruction. The article is not an indictment but an invitation to take action, and especially looks at how pornography and prostitution construct sexuality, kill imagination and perpetuate abuse.